Tauberian Constants for Some Double Hausdorff Matrices - Rhoades, B.; Thorpe, B. (Sarajevo Journal of Mathematics, 2017)
Mirza and Thorpe [9], obtained the Tauberian constant for C(1, 1) summability for sequences satisfying the boundedness condition (m^2 + n^2)a_mn = O(1). In this paper we investigate the analogous questions for double Hausdorff matrices.